Pacific worlds : a history of seas, peoples, and cultures - Matsuda, Matt K. (Cambridge ; New York : Cambridge University Press, 2012)
'Asia, the Pacific Islands and the coasts of the Americas have long been studied separately. This essential single-volume history of the Pacific traces the global interactions and remarkable peoples that have connected these regions with each other and with Europe and the Indian Ocean, for millennia. From ancient canoe navigators, monumental civilisations, pirates and seaborne empires, to the rise of nuclear testing and global warming, Matt Matsuda ranges across the frontiers of colonial history, anthropology and Pacific Rim economics and politics, piecing together a history of the region. The book identifies and draws together the defining threads and extraordinary personal narratives which have contributed to this history, showing how localised contacts and contests have often blossomed into global struggles over colonialism, tourism and the rise of Asian economies. Drawing on Asian, Oceanian, European, American, ancient and modern narratives, the author assembles a fascinating Pacific region from a truly global perspective'--
Introduction: encircling the ocean -- 1. Civilization without a center -- 2. Trading rings and tidal empires -- 3. Straits, sultans and treasure fleets -- 4. Conquered colonies and Iberian ambitions -- 5. Island encounters and the Spanish lake -- 6. Sea changes and spice islands -- 7. Samurai, priests, and potentates -- 8. Pirates and raiders of the eastern seas -- 9. Asia, America, and the age of the galleon -- 10. Navigators of Polynesia and paradise -- 11. Gods and sky piercers -- 12. Extremities of the Great Southern Continent -- 13. The world that Canton made -- 14. Flags, treaties, and gunboats -- 15. Migrations, plantations, and the people trade -- 16. Imperial destinies on foreign shores -- 17. Traditions of engagement and ethnography -- 18. War stories from the Pacific theater -- 19. Prophets and rebels of decolonization -- 20. Critical mass for the earth and ocean -- 21. Specters of memory, agents of development -- 22. Repairing legacies, claiming histories -- Afterword: world heritage.
Includes bibliographical references (p. [379]-412) and index.
Keywords: Pacific Area -- Civilization; Pacific Area -- History